The Relationship Between Nutritional Status, Smoking Habits and Age on the Physical Fitness of Workers in the Tuban Cement Industry - Moh. Sholakhuddin; Indriati Paskarini (Poltekkes Kemenkes Surabaya, 2025)
Physical fitness is the body's ability to perform diurnal work effectively and efficiently over a long period of time without excessive fatigue. Based on the results of periodic health checks of workers of one of the Cement Companies in 2023, it shows that the physical fitness of workers is mostly at a very low level, namely 34.4%. This study aims to analyze the influence of age, body mass index, and smoking habits on the physical fitness of workers in a cement company in Tuban. The research design uses analytical observational studies with a cross-sectional approach. Data was obtained from routine health checks on 688 workers. The results showed that there was a significant relationship between age and smoking habits on physical fitness (p<0.05), while there was no significant relationship with nutritional status. The majority of workers have very low physical fitness (34.4%) and level I obesity status (52.11%). The study recommends a health promotion program to improve workers' physical fitness.